Reclaiming experiment: geographies of experiment and experimental geographies - Jellis, T (2013)
This thesis investigates the injunction to experiment in the social sciences and, more specifically, geography. This is both a geography of certain ways of thinking experiment, and an exploration of how particular strands of geographical thinking are being re-imagined and reworked as experimental under the influence of ideas and practices from within and beyond the discipline. Against the backdrop of recent debates about the status of experiment, it poses a number of key questions about what it means to be experimental, how experimental practices emerge and travel, and how these processes are inflected by the organization and atmospheres of particular sites of experimentation. These questions are addressed through a form of attentive participation at four key sites: The SenseLab and the Topological Media Lab in Montreal, the Institut für Raumexperimente in Berlin, and FoAM in Brussels. Based upon these encounters, and drawing upon the work of a range of exemplary experimentalists, the thesis develops the argument that there are new spaces of experiment which are worthy of such examination as part of a renewal of experimentation within geographical thinking. As such, the thesis outlines the logics of these forms of experiment and proposes the notion of ecologies of experiment. It also speculates on the possibilities for re-imagining what constitutes a geographical experiment, foregrounding the necessity of reactivating experiment as an ongoing ethos that needs careful cultivation and tending.